DNA barcodes highlight the role of glacial cycles on avian diversification and speciation in southern South America - Lijtmaer, Dario A (2024)
Fil: Lijtmaer Dario A. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia", CABA, Argentina